Tom Swift and His Airship - Appleton, Victor (Salt Lake City, UT : Project Gutenberg, 2002)
"Tom Swift and His Airship" by Victor Appleton is a novel in the original Tom Swift series. Young inventor Tom Swift completes the Red Cloud, a revolutionary hybrid airship combining dirigible and airplane technology. Just as he prepares for a cross-country test flight, the Shopton bank is robbed and Tom becomes the prime suspect. Now airborne and branded a fugitive, he must race back home to clear his name while evading those who would shoot him down. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Tom_Swift_and_His_Airship
Release date is 2002-01-01
Produced by Tom Szolyga
Keywords: Adventure and adventurers -- Juvenile fiction; Swift, Tom (Fictitious character) -- Juvenile fiction; Airships -- Juvenile fiction